Entire coronary origin from the right sinus of Valsalva as a common trunk in an ex-competitive athlete - Morales-Solano, Eddy; Cabrera-Rego, Julio Oscar; Gandarilla-Sarmientos, Julio César; Olivares-Aquiles, Eddy W. (SA Heart Journal, 2017)
54-year-old male patient presenting with typical ischaemic chest pain.